2014
DOI: 10.4172/2329-6836.1000128
|View full text |Cite
|
Sign up to set email alerts
|

Rubiothiazepine a Novel Unusual Cytotoxic Alkaloid from Ixora undulata Roxb. Leaves

Abstract: Leaves of Ixora undulata Roxb. were investigated phytochemically for the first time for its alkaloidal content, which resulted in the isolation of a novel unusual thiazepine alkaloid glycoside identified as 7-[(β-D-glucopyranosyl)oxy]-6-hydroxy-2-methoxy-4,5-dihydro-1,3-thiazepine and trivially named as Rubiothiazepine. Its structure was determined on the basis of 1D and 2D NMR ( 1 H-, 13 C-NMR, 1 H-1 H COSY, 1 H-13 C HETCOR, 1 H-13 C HMBC, 1 H-15 N HMBC and DIFNOE), high resolution ESI-CID-MS/MS, UV and IR sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…have reported that plant metabolites such as catechin and coumarin may serve as co-metabolites for polychlorinated biphenyl (PCB) degrading bacteria. More so, thiazepines which are substituted thiepins have been reported to act as phytoalexins(Pedras and To 2015) Mohammed et al (2014). opined that thiazepine type alkaloids are rare in nature and most of the known thiazepine rings occur in 1,4-form and generally fused with other substituents like benzene.…”
mentioning
confidence: 99%
“…have reported that plant metabolites such as catechin and coumarin may serve as co-metabolites for polychlorinated biphenyl (PCB) degrading bacteria. More so, thiazepines which are substituted thiepins have been reported to act as phytoalexins(Pedras and To 2015) Mohammed et al (2014). opined that thiazepine type alkaloids are rare in nature and most of the known thiazepine rings occur in 1,4-form and generally fused with other substituents like benzene.…”
mentioning
confidence: 99%